Geometric stone settings in the Yustyd Valley and its surroundings (Altai Mountains, Russia): Bronze Age 'virtual dwellings' and associated structures. (June 2017) - Bourgeois, Jean; De Langhe, Kaatje; Ebel, Alexander V.; Dvornikov, Eduard P.; Konstantinov, Nikita; Gheyle, Wouter
Abstract: Geometric stone settings are one of the striking monuments in the Altaian landscape. A lot of structures have been recorded, but no function or date has been defined for them. In the literature, they are known under very different names and dates. We suggest calling them 'virtual dwellings'. Several arguments have proposed a date, varying from the Late Bronze Age to the medieval period. The monument type is recorded mainly in the higher Altai Mountains (esp. Kosh-Agatch rayon), in Western Mongolia and in Tuva. A recent detailed survey in the valley of Yustyd and its surroundings allowed to set up a basic description of the type and some related types. Recent excavation suggests a date in the Early Bronze Age. According to E. Jacobson-Tepfer's suggestion, we propose that these monuments are ritual monuments, in a funerary context, possibly as location for exposition of the body or sky burials.